Concept of Islamic Character Education According to The Thoughts of Khalid Bin Hamid Al-Hazami And Hasyim Ali Al-Ahdal - Fadhlurrahman Fadhlurrahman; Tri Yaumil Falikah; Zalik Nuryana; Reza Amin Nur Ihsan; Asih Kartika Putri; Roihanah Roihanah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
The development and refinement of the concept of character education between characters continue to interact and reinforce each other. This study aims to describe the idea of character education between Khalid Bin Hamid Al-Hazami and Hasyim Ali Al-Ahdal. They are both Muslim leaders and developed the concept of Islamic character education. The research methodology was carried out by taking primary data from books written by the two figures, then translating and interpreting by strengthening the thoughts of various other figures. The findings of this study are several factors that influence the formation of Islamic character, the purpose of forming Islamic character to the values contained in Islamic character. There are three stages in the cultivation of Islamic character education. First, instill in the students' hearts the burden of law from God. Second, students must be enthusiastic about undergoing God's punishment. Third, the emergence of students' strong desire to get a great reward from Allah. In addition, Khalid bin Hamid al-Hazami explained that the cultivation of character education is not hereditary but is instilled through education. If students make mistakes during the character education process, there are five stages of punishment—implementation of this concept in formal and non-formal educational institutions. The implications of this research will be a new color for the idea of character education that has existed so far.